2009
DOI: 10.1007/s10549-009-0404-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variation in mitotic kinases with breast cancer risk

Abstract: An RNAi based functional screen of mitotic kinases in Drosophila recently identified a number of members of the kinome that are required for normal cell division. Depletion of these kinases resulted in a number of different mitotic abnormalities including spindle malformation, chromosome missegregation, centrosome amplification and failure of cytokinesis [1]. Since mitotic defects are commonly observed in cancer cells, these kinases may contribute to tumor development and/or progression. To investigate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Other major related key genes identified in our study, including FYN, CAV1, HSPG2, and MMP2, have been reported to be dysregulated or involved in some important biological processes in breast cancer (Wang et al, 2010;Rao et al, 2012;Hu et al, 2013;Slattery et al, 2013), which were consistent with our results. For example, the loss of caveolin-1 (CAV1) in cancer associated fibroblasts (CAFs) is associated with the induction of the autophagic program by activating the HIF1α and NFkB, then causes the production of highly energetic nutrients to support cancer cell growth (Morandi and Chiarugi, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Other major related key genes identified in our study, including FYN, CAV1, HSPG2, and MMP2, have been reported to be dysregulated or involved in some important biological processes in breast cancer (Wang et al, 2010;Rao et al, 2012;Hu et al, 2013;Slattery et al, 2013), which were consistent with our results. For example, the loss of caveolin-1 (CAV1) in cancer associated fibroblasts (CAFs) is associated with the induction of the autophagic program by activating the HIF1α and NFkB, then causes the production of highly energetic nutrients to support cancer cell growth (Morandi and Chiarugi, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Here, we examined key candidate genes encoding angiogenesis factors (9, 10) mitotic kinases (11), growth stimulatory mediators and stromal factors (12, 13), as well as genes and regions suggested by expression studies (14) and genome-wide association studies (1517). We first evaluated the association between mortality and inherited single nucleotide polymorphism (SNP) variation among invasive epithelial ovarian cancer patients seen at the Mayo Clinic, and we pursued key findings via analysis of data from The Cancer Genome Atlas (TCGA).…”
Section: Introductionmentioning
confidence: 99%
“…To explore this hypothesis we evaluated associations between tagging SNPs (r 2 >0.8) from over 200 genes encoding proteins implicated in the mitotic process in breast cancer cases and unaffected controls from the Mayo Clinic Breast Cancer Study. We identified 34 SNPs from 33 genes that displayed significant associations with breast cancer risk (p<0.01) (18, 19). Here, we further evaluated the contribution of SNPs in mitotic regulators to cancer by assessing associations between these 34 SNPs and pancreatic cancer risk in a rapid ascertainment clinic-based study of 1,143 pancreatic cancer cases and 1,097 unaffected controls from the Mayo Clinic.…”
Section: Introductionmentioning
confidence: 99%